2007
DOI: 10.1007/s10341-007-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical thinning of apple with new compounds

Abstract: While at present the strategies for thinning the main apple cultivars are based on carbaryl, from 2008 onwards growers will have to try to achieve adequate crop load without this well known compound. The tank-mix NAA + benzyladenine proved to be an option for thinning difficult cultivars like 'Fuji' by using active ingredients that will still be available after 2008. Intensive but selective thinning occurred using metamitron, an a. i. currently registered as herbicide that has been recently proposed by the EUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 1 publication
8
12
0
1
Order By: Relevance
“…In preliminary experiments performed on cv Red Chief, MET was shown to be an effective thinner in this genotype (A. Dorigoni, personal communication), as observed in other apple cultivars (Dorigoni and Lezzer, 2007). This experimental scheme is suitable for the purposes of this study because it provides fruitlet populations with diverse genetic backgrounds and APs, obtained either from the natural availability or through different chemical treatments.…”
Section: Fruit Drop Dynamicsmentioning
confidence: 87%
“…In preliminary experiments performed on cv Red Chief, MET was shown to be an effective thinner in this genotype (A. Dorigoni, personal communication), as observed in other apple cultivars (Dorigoni and Lezzer, 2007). This experimental scheme is suitable for the purposes of this study because it provides fruitlet populations with diverse genetic backgrounds and APs, obtained either from the natural availability or through different chemical treatments.…”
Section: Fruit Drop Dynamicsmentioning
confidence: 87%
“…The effect of metamitron applied alone or in tank mix with BA or NAA on fruit maturity parameters of young 'Golden Delicious' apples in three experimental years. some growing conditions double metamitron treatment in high concentration can cause overthinning (Dorigoni and Lezzer, 2007;Basak, 2011). Combined application of metamitron and BA as well as the combination of metamitron and NAA in standard rates caused sufficient fruit abscission.…”
Section: Treatmentmentioning
confidence: 99%
“…The second approach was to test the use of Brevis developed by Makhtashim Agan, a specially formulated thinning agent containing the photosynthesis inhibitor metamitron as active ingredient. Studies with an herbicide-formulation of metamitron have shown the potential use of metamitron for thinning apples (Clever, 2007;Dorigoni and Lezzer, 2007;Köpcke, 2005).…”
Section: Introductionmentioning
confidence: 99%